Association Between Digoxin Use and Cancer Incidence: A Propensity Score-Matched Cohort Study With Competing Risk Analysis - Tai, Chi-Jung; Yang, Yi-Hsin; Tseng, Tzyy-Guey; Chang, Fang-Rong; Wang, Hui-Chun (Frontiers in Pharmacology, 2021)
Background: Previous studies neglected death as a critical competing risk while estimating the cancer risk for digoxin users. Therefore, the current study aims to assess the effectiveness of digoxin on cancer prevention by competing risk analysis. Methods: We performed a population-based retrospective cohort study using the Taiwan National Health Insurance Research database between 1998 and 2010. After one-to-one propensity score-matching from 36,160 patients with defined criteria, we enrolled 758 patients both in digoxin and β-blocker group for further analysis. Results: The results showed that the digoxin group had higher all-cause mortality than the β-blocker group in the 4- year (10.4 vs. 4.9%) and 8 years (13.6 vs. 7.0%) follow-up. The subdistribution HR of cancer incidence in the digoxin group compared to the β-blocker group was 1.99 (95% confidence interval [CI]: 1.22–3.01) and 1.46 (95% CI: 1.01–2.15) in the 4 years and 8 years follow-up, respectively. Conclusions: The result of our study showed the usage of digoxin has no benefit in cancer prevention compared with β-blocker. The possibility of β-blocker as a new drug candidate for cancer prevention needs further clinical evaluation. The current study also emphasized the necessity of competing risk analysis applying to similar clinical researches.